(3GdWHbGJ GdcHQis - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s ((3eMeO Hf GSeGYjd Hf MSf Hf Ydi Hf CHj GdMSjf GdgQbdi s)
(3ChdgG (B:s
(3GNHQfG GdTjN GHh eMeO bQCI Ydjg PcQ ef GfJei Gdjg QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3fRd Ydjg GfG aJMfG dc aJMG eHjfkG abGd LHQjd fgfFc jG QShd Gddg hgfGg GdeSdehf s
(3Ydjg bQBAGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1103s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI edi (B(424) s
Keywords: (3GdJGQjNs